2018
DOI: 10.1007/s00267-018-0998-5
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Divide: Challenges and Opportunities for Public Sector Agricultural Professionals Working with Amish and Mennonite Producers on Conservation

Abstract: As Amish and Old Order and Conservative Mennonite (i.e., Plain) farmers increase their presence in the agricultural sector, it is crucial for public sector agricultural professionals to effectively work with them to mediate nonpoint source pollution and address issues like the hypoxic zone in the Gulf of Mexico. However, there is a dearth of research on how public sector agricultural professionals can better work with Plain producers on environmental management. There are also few training resources for those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…These studies clarified that because nonoperating landowners tend to rely less on income from the land compared with producers, conservation practice adoption is less risky for them; therefore, financial incentives were less important. Second, one study showed that charging, not giving, money promoted adoption among Plain Sect farmers in the United States, who generally do not accept government money (Brock et al., 2018). This study documented making horse‐drawn no‐till drill available for Plain Sect farmers to rent, rather than buy from a retailer, helped to promote adoption and avoid direct government payments.…”
Section: Resultsmentioning
confidence: 99%
“…These studies clarified that because nonoperating landowners tend to rely less on income from the land compared with producers, conservation practice adoption is less risky for them; therefore, financial incentives were less important. Second, one study showed that charging, not giving, money promoted adoption among Plain Sect farmers in the United States, who generally do not accept government money (Brock et al., 2018). This study documented making horse‐drawn no‐till drill available for Plain Sect farmers to rent, rather than buy from a retailer, helped to promote adoption and avoid direct government payments.…”
Section: Resultsmentioning
confidence: 99%
“…We found that organic farmers rely more on organic industry veterinarians when they are just converting, but it would be interesting to track organic farms throughout the transition process to document how their animal health concerns and practices evolve (Bennedsgaard et al, 2003). Tailoring veterinary outreach to address cultural and religious sensitivities can also be important in this research area, given that many of the producers were Amish, where relationships and in-person interactions can be even more important (Brock et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Given the significant number of Amish organic corn farmers in these states, organic farming outreach programs should consider ways to adapt content to the unique cultural and religious beliefs of this population, and modes of dissemination should focus on or include printed products and in-person farmer meetings [51]. While national studies suggest that organic farmers had higher levels of formal education than conventional farmers [7], Amish producers traditionally prefer experiential and home-based learning, have lower levels of formal schooling, and English is typically their second language [52].…”
Section: Discussionmentioning
confidence: 99%
“…It also would be helpful to work with local leaders within the community to help distribute written materials and/or to organize workshops. Additionally, conservation tillage and soil health research and outreach efforts should be adapted to farmers who rely on horse-drawn implements [51].…”
Section: Discussionmentioning
confidence: 99%